Halal Branding Construct and It’s Influence on Purchase Intention and WoM in Indonesia - Kusmayadi, Hery; Albari (Journal of Business and Management Review, 2024)
Research Aims: The purpose of this study is to explain the positive influence of Halal branding constructs, namely Halal Brand Perceived Quality, Halal Brand Image, and Halal Brand Trust, on Purchase Intention and Word of Mouth. Design/methodology/approach: The research adopts an empirical approach, using convenience sampling with 313 respondents from Indonesian citizens across major islands. Data processing employs Structural Equation Modelling (SEM) with AMOS 24 software. Research Findings: The findings indicate that Halal Brand Perceived Quality, Halal Brand Image, and Halal Brand Trust have a positive and significant impact on Purchase Intention and Word of Mouth. Halal Brand Perceived Quality positively and significantly affects Halal Brand Image and Halal Brand Trust. While Halal Brand Image has a positive and significant influence on Halal Brand Trust, the latter does not affect Word of Mouth. Purchase intention also has a positive and significant impact on Word of Mouth. Theoretical Contribution/Originality: These findings expected to develop a theoretical framework derived from traditional brand constructs and test it on Halal brands with a focus on implementation in Indonesia. It can provide insights for marketers to enhance and improve Halal Brand Perceived Quality, Halal Brand Image, and Halal Brand Trust, ultimately boosting product sales and promote positive Word of Mouth. Marketers can implement Halal certification programs, enhance food safety systems, update brand propositions, and engage in targeted communication with consumers to strengthen positive perceptions, brand image, and consumer trust in Halal brands. Keywords: Halal brand image, Halal brand perceived quality, Halal brand trust, Purchase intention, Word of Mouth.